CANCER: ENVIRONMENTAL AND HABIT-LINKED CAUSES - Mitra, Jaganmay (SCHOOL SCIENCE, 2013)
Cancer today is one of the most dreaded diseases the mankind has been suffering from. It is, in fact, a collection of diseases that take a heavy toll of human life. At present, one-fifth of the total human deaths in the world is due to cancer. This situation has compelled thousands of cancer researchers to undertake strenuous round-the clock research to investigate the definite causative organisms or the causal factors behind more than a hundred types of human cancer.